Simultaneous determination of eight bioactive bakkenolides of Petasites tatewakianus Kitam by HPLC-UV - Jianming He; Qin Wang; Yan Wang; Ruibing Chen; Yuyang Zhang; Meili Guo (Elsevier, 2013)
A high-performance liquid chromatography coupled with variable wavelength detection (HPLC-UV) was developed to evaluate the quality of Petasites tatewakianus Kitam through a simultaneous determination of eight bakkenolides: bakkenolide-L, bakkenolide-D, bakkenolide-B, bakkenolide-Ia, bakkenolide-VIIa, bakkenolide-IVa, bakkenolide-IIIa and homofukinolide. With a C18 analytical column, the eight analytes were efficiently separated using tetrahydrofuran-acetonitrile-water as the mobile phase in a constant program. The limits of detection and limits of quantitation of the method ranged 0.42-2.56 μg/mL and 1.22-8.40 μg/mL, respectively. The intra- and inter-day precisions of the method were all less than 1.83%. All the recoveries for the spiked analytes ranged 97.8%-102.4%. There were statistically significant differences among the contents of the eight bakkenolides in different parts and origins of P. tatewakianus (P<0.01). The content of total bakkenolides in rhizome was higher than that in other parts of the plant. The content of total bakkenolides in rhizome from Baishan was higher than those in other localities. The result suggested that rhizome may be the most valuable part of P. tatewakianus, and P. tatewakianus from Baishan may be the best plant resource. Our results might serve as a sound foundation for further study and application of this plant.